On Rock and Book and Leaf: Reading Ondaatje’s Handwriting - Vigurs, Rochelle (Studies in Canadian Literature, 2001)
Considered within the context of his earlier works, Michael Ondaatje’s collection of poetry Handwriting is at first surprising and unpredictable. While his work has followed an arc of accumulating self-exposure, Handwriting, rather than acting as a culmination of this process, is a work in which the self is again defaced. In Handwriting, Ondaatje considers the notion of selfhood by sublimating the authorial voice – a technique that allows an inclusive pluralism to arise. In Handwriting, Ondaatje explores ideas of place and the imaginative interpretation of it, different patterns of sound and form, and the ways personal history fuels the artistic process. In its minimalist aesthetic and fragmented poetics, Handwriting casts a singular light on the individual manifestation of selfhood while setting in motion a rhythm that incorporates the voice of collective memory.